Light pollution in Pomurje statistical region - Žiberna, Igor; Ivajnšič, Danijel (Journal for Geography, 2020)
The article discusses the state of light pollution in the Pomurje statistical region in 2019. We analyzed the radiance parameter by statistical regions in Slovenia and by municipalities within the Pomurje statistical region based on the night channel data of the Suomi satellite. Radiance data on the municipal level were correlated with the public road network. The brightest and darkest areas were identified. However, the results show significant differences in radiance in the Pomurje statistical region, with less intense light pollution in Goričko and more illuminated area in the surrounding larger settlements.